MASSIVE PRIMARY LEIOMYOSARCOMA ON CAVUM THORAX : A VERY RARE CASE - Atin, Fulgensius; Prasetyanto, R. Dhany; Valerie Gunawan, Alyssa Claudia; Goenawan, Monica (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
The cavum thorax primary leiomyosarcoma is extremely rare and unusual case. leiomyosarcoma as smooth muscle carcinoma could be comes from various part of body as primary site, but in the case of cavum thorax leiomyosarcoma its estimated only 1-4 of all soft tissue sarcoma. In this report we present a 69 years old woman came to the outpatient clinic with a big lump in the chest. This lump has been felt for 1 year and was a big and bizarre looking tumor, pain was felt in the right chest with intensity of 4-5 visual analog scale. Difficulty to breath and shortness of breath was not complained by the patient, nausea and vomiting was not complained. The patient has a history of uterine tumor that has been done by surgery. Diagnostic test of Multidetector Computed Tomography (MDCT) scan and ultrasonography has been done in this patient, and show a suggestive malignant soft tissue tumor. The surgery has been done with preoperative internal mammary artery embolization to prevent massive bleeding. A 15 cm length, 9 cm wide and 500 grams of weight tumor was evacuated. The immunohistochemistry examination was performed to the tumor specimen, and the result was a leiomyosarcoma tissue. A good examination, early detection with adequate diagnostic tools and adequate surgery as the only option of treatment is a predicting factor of successful treatment, due to lack of treatment option and ineffectiveness use of adjuvant therapy.